Effects of ΔNp63 Gene Down-expression on Invasion of Bladder Carcinoma Cells in Vitro - Jing, Peng; Zou, Jiaqiong (Urology Journal, 2020)
Purpose: This work aims to investigate the effects of ΔNp63 gene down-expression on invasion of bladder carcinoma cells in vitro. Materials and Methods: Bladder carcinoma cell lines UM-UC-3 and 5637 were cultured. The expression plasmids encoding ΔNp63 were constructed and transfected into UM-UC-3 and 5637 cells. The migration and adhesion of cells were detected. The expressions of ΔNp63 and invasion-related zonula occludens protein-1 (ZO-1) in cells were determined by real-time polymerase chain reaction (PCR) and western blot analysis. Confocal microscopy was used to observe the location of ZO-1 in cells. Results: Results showed that the down-expression of ΔNp63 reduced the migration of UM-UC-3 and 5637 cells, decreased the heterogeneity adhesion, and increased homogeneous adhesion. After transfection with ΔNp63, the ZO-1 expression in cell membrane and cell cytoplasm was inhibited, also the ZO-1 mRNA and protein levels in cells were significantly decreased. Conclusion: This study indicates thatΔNp63 gene down-expression can reduce the invasion of bladder carcinoma cells in vitro.